Methods for improving writing competence through the use of multimodal composition - Ziroat , Saliyeva (The Lingua Spectrum, 2025)
This article explores the use of multimodal composition as an innovative approach to enhancing writing competence among students. Multimodal composition, which integrates various modalities such as text, images, audio, video, and interactive elements, offers a dynamic way to develop students’ creativity, critical thinking, and technological skills. The article discusses several effective methods for incorporating multimodal composition into the classroom, including Project-Based Learning (PBL), Collaborative Writing, Inquiry-Based Learning, Digital Storytelling, and Media Analysis. These methods not only improve students’ writing abilities but also foster media literacy, collaboration, and problem-solving skills. The article also highlights the role of modern technologies, such as online platforms, video editing software, and interactive presentation tools, in facilitating multimodal learning. By adopting these strategies, educators can create a more engaging and interactive learning environment, preparing students to meet the demands of the modern world. This article provides practical insights and methodologies for educators aiming to enhance their students’ writing competence through multimodal approaches.